Kajian Korosi Struktur Conveyor B pada Tambang Batubara PT GHI di Kabupaten Tapin, Provinsi Kalimantan Selatan - Rizkal Zubair; Elfida Moralista; Nuur Isniarno (Bandung Conference Series: Mining Engineering, 2022)
Abstract. Conveyor structure is a tool that is applied to the mining industry as a tool to move goods or materials or minerals such as coal from one place to another. Conveyor structure is made of metal material that can experience corrosion. Therefore, the need for a method of controlling corrosion and monitoring corrosion on the conveyor structure, so that corrosion can be controlled. The purpose of this research is to determine the type of corrosion that occurs in the conveyor structure, to determine the corrosion control method, to determine the corrosion rate and the remaining service life of the conveyor structure. The methodology used in this study is measuring the thickness reduction of the conveyor structure. This research was conducted on a conveyor structure of 90 meters above ground level. Measurement of the thickness of the conveyor structure using the Ultrasonic Thickness Gauge TT 130 at 25 observation points. The environmental conditions in the research area are the air temperature in the range of 32 oC-33 oC, while the rainfall is in the range of 6-11 mm. The type of corrosion that occurs in the conveyor structure is uniform corrosion. In controlling this corrosion using a coating method with Seaguard 5000 primer coating, Sherglass FF intermediate coating, and aliphatic acrylic modified polyurethane top coating. Abstrak. Conveyor adalah alat yang digunakan pada industri pertambangan sebagai alat untuk memindahkan barang atau material atau bahan galian contohnya batubara dari suatu tempat ke tempat yang lainnya. struktur conveyor terbuat dari material logam yang rawan mengalami korosi. Oleh karena itu, diperlukan metoda pengendalian korosi serta monitoring korosi pada struktur conveyor, sehingga korosi dapat dikendalikan. Tujuan dilakukannya penelitian ini adalah untuk mengetahui jenis korosi yang terjadi pada struktur conveyor, mengetahui metode pengendalian korosi, mengetahui laju korosi dan sisa umur pakai struktur conveyor. Metodologi yang digunakan dalam penelitian ini yaitu pengukuran pengurangan ketebalan struktur conveyor. Penelitian ini dilakukan pada struktur conveyor sepanjang 90 meter yang berada di atas permukaan tanah. Pengukuran ketebalan struktur conveyor menggunakan alat Ultrasonic Thickness Gauge TT 130 pada 25 test point. Kondisi lingkungan di daerah penelitian yaitu temperatur udara berkisar 32 oC-33oC, sedangkan curah hujan berkisar 6-11 mm. Jenis korosi yang terjadi pada struktur conveyor adalah korosi merata. Dalam pengendalian korosi ini menggunakan metoda coating dengan primer coating Seaguard 5000, intermediate coating Sherglass FF, dan top coating aliphatic acrylic modified polyurethane.